Leadership credibility and change success: mediating role of commitment to change - Ouedraogo, Noufou; Zaitouni, Michel; Ouakouak, Mohammed Laid (My University, 2021)
The purpose of this study is to investigate the effects of leadership credibility on employees' behaviours and attitudes towards organisational change through the lens of employee commitment to change.
Keywords: leadership credibility; employee commitment to change; affective commitment to change; normative commitment to change; continuance commitment to change; change success